2021
DOI: 10.3906/sag-2102-328
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to colchicine treatment is a common misevaluation in familial Mediterranean fever

Abstract: Background: Familial Mediterranean fever (FMF) is a hereditary autoinflammatory disease that requires lifelong colchicine treatment. Colchicine is the mainstay of the treatment which decreases the frequency and the severity of recurrent FMF attacks, also, prevents the development of amyloidosis. This study aimed to investigate the rates of colchicine treatment adherence in patients with FMF and the factors related to treatment non-adherence. Materials and methods: This observational study was conducted with 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Various factors like disease pattern, severity, administration route of the drug, side effects, patient demographics, socioeconomic status, knowledge and perception regarding the drug may affect the patient's compliance [10][11][12][13]. Similarly, in FMF adherence to colchicine varies between 33.3-51.5 % [14][15][16][17]. Furthermore, rate of true colchicine resistance reported to reduce to 5 % from 5-15 % in FMF, when patients were questioned for drug adherence and non-adherent patients were excluded [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors like disease pattern, severity, administration route of the drug, side effects, patient demographics, socioeconomic status, knowledge and perception regarding the drug may affect the patient's compliance [10][11][12][13]. Similarly, in FMF adherence to colchicine varies between 33.3-51.5 % [14][15][16][17]. Furthermore, rate of true colchicine resistance reported to reduce to 5 % from 5-15 % in FMF, when patients were questioned for drug adherence and non-adherent patients were excluded [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Among the observed cohort of diabetic patients, the proportion of high-adherent patients diagnosed with several concomitant diseases exceeded the proportion of low- and middle-adherent patients. Other studies also found that medication adherence was higher among patients “with” in comparison with those “without” concomitant diseases, probably due to their increased concerns about worsening in their condition [ 29 , 30 ]. The odds of medication adherence among patients with chronic conditions taking four medicines are higher than those taking one medicine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors could contribute to insufficient response to colchicine: lack of compliance, the occurrence of side effects, drug interactions, genetic factors, and environmental factors (infections, stress, and diet) ( 131 ). All studies and definitions agree that a maximum tolerated dosing of colchicine ( 132 ) and the assessment of compliance are the prerequisites before discussing crFMF ( 133 ), but finding a standardized way is challenging ( 134 ). Missing tablet count, Morisky score ( 135 ), and colchicine dosage in the hair were rarely reported in our study.…”
Section: Discussionmentioning
confidence: 99%